THE EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING ON CORPORATE SUSTAINABILITY - Hery Syaerul Homan (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
The purpose of this research is to look into the impact of Environmental Management Accounting on company sustainability. The sample in this study was taken using a purposive sampling technique. The research sample is a company registered on the IDX for the 2018-2021 period. Out of a total of 740 existing companies, only 16 companies met the criteria, so the number of samples in this study were 16 companies observed in four observation years, namely 2018 - 2021. All of these companies were INCO, PTBA, BUMI, ANTM, ITMG, TINS, PTRO, ANJT, JPFA, AALI, PGAS, JSMR, ABMM, WIK, INTP and ASII. The research data were obtained from the company’s financial statements and analyzed using panel regression analysis techniques. The findings of this study show that environmental management accounting positively impacts corporate sustainability in terms of both social and environmental factors. companies that have low Environmental Management Accounting.